Performance reporting: a review of literature in the public sector and statutory bodies / Saflina Azis, Mustafa Kamal Mat and Syahida Md Zeni - Azis, Saflina; Mat, Mustafa Kamal; Md Zeni, Syahida (2016)
This paper reviews the literature on performance reporting in the public sector. The performance reporting is one of the techniques used in measuring the performance of organization. It is a mean to discharge the accountability of the organization to the public. It is hope that this paper will provide guidance in understanding about the performance reporting practices in public sector as well as statutory bodies.